(untitled) (CIPEEX, 2025)
Introduction: The study of medicinal plants involves several areas of science since, although currently included in the List of Medicinal Plants of Interest to the Brazilian Unified Health System (SUS), there is a lack of pharmacobotanical studies that can support their quality control. Morphological analyses were performed on fresh material with the aid of a stereomicroscope. Objective: To describe the morphology of the root and stem of Justicia pectoralis. Methodology: This is a descriptive and qualitative study, and the morphological study followed the methodologies for this description based on organographic characters. Results: The root is axial and the stem is stalk-like or scape-like. In cross section, the root of J. pectoralis has a single-layered epidermis, well-developed intercellular spaces, and a collateral vascular system with a protostelic organization. The stem has a uniseriate epidermis with simple multicellular trichomes and cystoliths. Adjacent to the epidermis is angular collenchyma. The vascular system is collateral with an ectophloic siphono-stele structure. Conclusion: The findings of this study allow us to infer that the presence of solitary globose cystoliths, observed in the stem of J. pectoralis, constitutes an anatomical marker of taxonomic relevance that can be used to characterize and distinguish the species under study.